PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR SISWA - Patrik Atena; Ali Imron; Yustika Sri Ekwandari (FKIP UNIVERSITAS LAMPUNG, 2015)
The purpose of this study was to determine whether there was a significant effect and the magnitude of the effect of the application of the model significance level of Contextual Teaching and Learning on the cognitive achievement of students in Class X History Lesson IIS Swadhipa Natar high school academic year 2014/2015. The method used was quantitative with a quasi-experimental design. Based on the analysis of quantitative data, it can be concluded that there was significant influence and magnitude of the effect of the application of the model significance level of Contextual Teaching and Learning was equal to 0.65.Tujuan penelitian ini adalah untuk mengetahui ada tidaknya pengaruh yang signifikan dan besarnya taraf signifikansi pengaruh penerapan model Contextual Teaching and Learning terhadap hasil belajar kognitif siswa pada Mata Pelajaran Sejarah Kelas X IIS di SMA Swadhipa Natar Tahun Pelajaran 2014/2015. Metode yang digunakan adalah kuantitatif dengan desain eksperimen semu. Berdasarkan analisis data secara kuantitatif dapat disimpulkan bahwa ada pengaruh yang signifikan dan besarnya taraf signifikansi pengaruh penerapan model Contextual Teaching and Learning adalah sebesar 0,65.Kata kunci: ctl, hasil belajar kognitif, model pembelajaran